2014
DOI: 10.1111/1462-2920.12358
|View full text |Cite
|
Sign up to set email alerts
|

Novel molecular determinants of viral susceptibility and resistance in the lipidome of Emiliania huxleyi

Abstract: Viruses play a key role in controlling the population dynamics of algae, including Emiliania huxleyi, a globally distributed haptophyte with calcite coccoliths that comprise ca. 50% of the sinking carbonate flux from the surface ocean. Emiliania huxleyi viruses (EhVs) routinely infect and terminate E. huxleyi blooms. EhVs are surrounded by a lipid envelope, which we found to be comprised largely of glycosphingolipids (GSLs) with lesser amounts of polar glycerolipids. Infection appears to involve membrane fusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
155
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 71 publications
(170 citation statements)
references
References 60 publications
13
155
1
Order By: Relevance
“…In vitro studies showed that the EhV-encoded SPT preferentially utilizes myristoyl-CoA as a substrate, rather than the classical host SPT that uses palmitoyl-CoA (Han et al, 2006). Indeed, production of viral-derived sphingolipids (e.g., vGSL) was recently demonstrated and suggested to have a functional role in viral assembly as they are major constituents of viral membranes (Vardi et al, 2009(Vardi et al, , 2012Fulton et al, 2014). Our metabolome analysis clearly indicated increased levels of fatty acids, amino acids, and glucose.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In vitro studies showed that the EhV-encoded SPT preferentially utilizes myristoyl-CoA as a substrate, rather than the classical host SPT that uses palmitoyl-CoA (Han et al, 2006). Indeed, production of viral-derived sphingolipids (e.g., vGSL) was recently demonstrated and suggested to have a functional role in viral assembly as they are major constituents of viral membranes (Vardi et al, 2009(Vardi et al, , 2012Fulton et al, 2014). Our metabolome analysis clearly indicated increased levels of fatty acids, amino acids, and glucose.…”
Section: Discussionmentioning
confidence: 69%
“…Specific fingerprinting of viral-derived sphingolipids revealed a unique signature of multihydroxylated C16-based long-chain base forms in infected cultures and natural populations (Vardi et al, 2012;Fulton et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under lytic infection however, viral glycosphingolipids (vGSLs) derived from myristoyl-CoA are synthesized de novo, and vGSLs are known to play a role in the regulation of cell death in infected cells and are enriched in the membrane of newly formed virions (Vardi et al, 2009;Fulton et al, 2014;Rosenwasser et al, 2014). These vGSLs were detected in coccolithophore populations in the North Atlantic, which highlights their potential as biomarkers for viral infection in the oceans (Vardi et al, 2009(Vardi et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%